A Mathematical Problem Condition: Truncated Triangles - Sümeyye Gürhan, Menekşe Seden Tapan Broutin (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2017)
The aim of this study is to investigate the types of cognitive apprehension that pre-service mathematics teachers have in the face of a mathematical problem situation and in what ways they use them, and to reveal that which developmental logic stages they have and how they operate on them according to types of apprehension they use. In this study, the case study was used because the results related to a certain situation were tried to be revealed. The data obtained were analyzed descriptively. 46 pre-service teachers who were enrolled in Elementary Mathematics Teaching Department in a state university located in the north-western part of Turkey participated in the study. In the study, the data was collected with worksheets distributed to pre-service mathematics teachers. According to findings of this study, each pre-service teacher uses different types of cognitive apprehension in the understanding of a given mathematical situation. It has also been observed that the pre-service teachers are operating at three different stages of developmental logic according to the types of apprehension. As a result of the research, it is partly revealed that the type of cognitive apprehension the students use when solving a geometric problem has an important effect on solving the problem. For this reason, in order to enable the students to reach the correct result in the event of a problem, firstly their perspective on problem and types of cognitive apprehension should be developed.